Penilaian Tingkat Kekeritisan Lahan Pertambangan dan Beberapa Pengguanaan Lahan Lainnya di Kalimantan Selatan - Subiq Kurniawan; Meldia Septiana; Muhammad Syarbini (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2024)
Critical land is land that is no longer productive from an agricultural perspective, because management and use do not consider land management requirements and soil conservation principles. This research aims to assess the level of criticality of land based on the level of erosion that occurs at various coal mining land locations in several districts in South Kalimantan. This research is non-experimental research using exploratory descriptive methods. The data collected is secondary data obtained through official publications from the Environmental Service and related agencies from several environmental documents of coal mining companies that have received approval from the authorized Agency. The secondary data used is the data needed to calculate the amount of erosion which is used as a basis for evaluating land criticality. These data include: soil texture, permeability, bulk density, rainfall, slope and slope length, management factors, land cover vegetation factors and soil organic C. Erosion estimation uses the Universal Soil Loss Equation (USLE) method. The results of erosion calculations using USLE show that in open mine land in Banjar Regency it is 233.9 tons ha-1 year-1, while in Tanah Laut Regency is 173.1 tons ha-1 year-1 and in Kotabaru Regency is 275.1 tons ha-1 year-1. The level of criticality of land in the mining area is at a critical and very critical level compared to natural land and cultivated land due to differences in erosion values ​​and also the thickness of the soil solum studied.